KEEFEKTIFAN MODUL PEMENTASAN MONOLOG BERBASIS KEARIFAN LOKAL DENGAN METODE ROLE PLAYING DAN TEKNIK 3M (MENIRU, MENGOLAH DAN MENGEMBANGKAN) - ., Hetilaniar; Murniviyanti, Liza (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2023)
his study resulted in a monologue staging module based on local wisdom for students of the Indonesian Language Education Study Program. As an independent study material, the module contains four main parts: the concept of a monologue, the activity of writing a monologue script idea, the practice of a monologue using the role playing method and 3M techniques, and a follow-up activity. The modules are developed based on the Borg and Gall development model. The procedure carried out is divided into four main stages, namely preliminary studies, module draft development, and validation to experts and practitioners, and effectiveness testing. To measure the effectiveness of the drama performance module in supporting students' mastery of drama appreciation. Students are given the task of making a monologue video at the end of teaching and learning activities as an evaluation tool. Based on the results and discussion of this study, the t-table data for the small group was 2.0, while the t-count was 9.7. So, tcount > ttable is 9.7 > 2.0. ttable in the large group is 1.695 and tcount is 165.2. So, tcount > ttable is 165.2 > 1.695. So it can be concluded that H0 is rejected and Ha is accepted, because there is a significant difference between student learning outcomes before and after using the monologue staging module, this also proves that the module is very effective in improving the learning outcomes of drama theory courses.